Death Denial in Bengali Cinema: A Terror Management Analysis of Srijit Mukherji’s Baishe Srabon and Hemlock Society - Ferdous, Reffat; Kareem, Saiyeed Shahjada Al (Social Science Review, 2023)
Everything that human beings do from the time of their birth, is a way for them to deny the inevitability of their death. A person adopts a myriad of ways to transcend the fear of death from their life and consciousness. This paper examines how the artistic medium of Bengali cinema provides insights into this existential issue and offers ways to overcome anxieties associated with human decay. Employing the Terror Management Theory (TMT) and film narratology, the study analyses two of Srijit Mukherji’s films, Baishe Srabon (2011) and Hemlock Society (2012), that involve plots where the characters explicitly encounter the fear of death. Both films substantiate TMT’s stance that humans seek immortality by establishing a “cultural worldview” and “self-esteem”, which provide individuals with an illusion of symbolic existence that will last even after their death. Social Science Review, Vol. 38(2), December 2021 Page 159-174